2019
DOI: 10.1097/aud.0000000000000720
|View full text |Cite
|
Sign up to set email alerts
|

Vestibular Function Modulates the Benefit of Hearing Aids in People With Hearing Loss During Static Postural Control

Abstract: Objectives: To evaluate the influence of auditory cues on postural sway in normal-hearing (NH) individuals, hearing-impaired individuals with vestibular impairment (HIVL), or hearing-impaired (HI) individuals without vestibular impairment. Design: Thirty-two participants received a hearing and a vestibular evaluation (vHIT, oVEMP, cVEMP) and then were separated in to three groups (NH, HI, HIVL). All participants had to stand on a force platform in four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
1
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(67 citation statements)
references
References 40 publications
4
56
1
6
Order By: Relevance
“…The 8 studies included 4 cross-sectional studies [Lacerda et al, 2012;Rumalla et al, 2015;Shayman et al, 2017;McDaniel et al, 2018], 3 cross-sectional controlled studies [Vitkovic et al, 2016;Negahban et al, 2017;Maheu et al, 2019], and 1 prospective nonrandomized study [Weaver et al, 2017]. The characteristics of included studies are demonstrated in Table 1.…”
Section: Results Of Search Strategy and Description Of Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…The 8 studies included 4 cross-sectional studies [Lacerda et al, 2012;Rumalla et al, 2015;Shayman et al, 2017;McDaniel et al, 2018], 3 cross-sectional controlled studies [Vitkovic et al, 2016;Negahban et al, 2017;Maheu et al, 2019], and 1 prospective nonrandomized study [Weaver et al, 2017]. The characteristics of included studies are demonstrated in Table 1.…”
Section: Results Of Search Strategy and Description Of Studiesmentioning
confidence: 99%
“…A total of 138 patients were HAs users. Ten out of 138 patients from one study were diagnosed with both SNHL and balance problems, documented by vestibular objective measurements (such as video head impulse test, caloric examination, cervical and ocular vestibular evoked myogenic potentials) [Maheu et al, 2019]. Twenty-five patients with hearing loss but non-HAs users were considered as a part of a control cohort only in one study [Negahban et al, 2017].…”
Section: Participantsmentioning
confidence: 99%
See 2 more Smart Citations
“…The intensity and frequency of sounds influencing postural regulation of stability is associated with the relationship between the vestibular system and organs of Corti in the inner ear [8]. Vestibular modulation by hearing aids has been documented to improve postural control in individuals with hearing loss [9]. However, changes in postural regulations by vestibular interference induced by sound effects are not evident in the elderly.…”
Section: Introductionmentioning
confidence: 99%